A General Overview on Non-coding RNA-Based Diagnostic and Therapeutic Approaches for Liver Diseases - Roy, Sanchari; Trautwein, Christian; Luedde, Tom; Roderburg, Christoph (Frontiers in Pharmacology, 2018)
Despite epochal progress in the treatment of hepatitis C virus infections, liver diseases still represent a major global health burden and an important cause of morbidity and lethality worldwide. Pharmacological treatment strategies for most liver diseases are still limited and new targets for prevention or treatment of liver disease are urgently needed. Non-coding RNA (ncRNA) such as miRNA or lncRNA have been shown to be deeply involved in the pathophysiology of almost all acute and chronic liver diseases. Recent data suggested a potential therapeutic use of miRNA by targeting different steps in the hepatic pathophysiology. In the present review, we summarize emerging insights of ncRNA in liver diseases. We also highlight examples of ncRNAs participating in the pathogenesis of different forms of liver disease and how they can be used as potential therapeutic targets for novel treatment paradigms. Furthermore, we describe an overview of up-to-date clinical trials and discuss about its future in clinical applications. Finally we highlight the potential role of circulating ncRNAs in diagnosis of liver diseases and discuss the major challenges and drawbacks that currently prevent the use of ncRNAs in clinical routine.